Genetic Analysis of Antibody Response to Porcine Reproductive and Respiratory Syndrome Vaccination as an Indicator Trait for Reproductive Performance in Commercial Sows - Sanglard, Leticia P.; Fernando, Rohan L.; Gray, Kent A.; Linhares, Daniel C. L.; Dekkers, Jack C. M.; Niederwerder, Megan C.; Serão, Nick V. L. (Frontiers in Genetics, 2020)
We proposed to investigate the genomic basis of antibody response to Porcine Reproductive and Respiratory Syndrome (PRRS) virus (PRRSV) vaccination and its relationship to reproductive performance in non-PRRSV infected commercial sows. 906 F1 replacement gilts (13917 days old) from two commercial farms were vaccinated with a commercial modified live PRRSV vaccine. Blood samples were collected about 52 days after vaccination to measure antibody response to PRRSV as sample-to-positive (S/P) ratio and for SNP genotyping. Reproductive performance was recorded for up to 807 sows for number born alive (NBA), number of piglets weaned, number born mummified (MUM), number stillborn (NSB), and number of pre-weaning mortality (PWM) at parities (P) 1 to 3 and per sow per year (PSY). BayesC0 was used to estimate heritability and genetic correlations of S/P ratio with reproductive performance. Genome-wide association study and genomic prediction were performed using BayesB. The heritability estimate of S/P ratio was 0.34±0.05. High genetic correlations (rg) of S/P ratio with farrowing performance were identified for NBA P1 (0.61), PWM P2 (-0.70), NSB P3 (-0.83), MUM P3 (-0.84), and NSB PSY (-0.90), indicating that genetic selection for increased S/P ratio would result in improved performance of these traits. A quantitative trait locus was identified on chromosome 7 (~25 Mb), at the Major Histocompatibility (MHC) region, explaining ~30% of the genetic variance for S/P ratio, mainly by SNPs ASGA0032113, H3GA0020505, and M1GA0009777. This same region was identified in bivariate GWAS of S/P ratio and reproductive traits, with SNP H3GA0020505 explaining up to 10% (for NBA P1) of the genetic variance of reproductive performance. The heterozygote genotype at H3GA0020505 was associated with greater S/P ratio and NBA P1 (P = 0.06), and lower MUM P3 and NSB P3 (P = 0.07). Genomic prediction accuracy for S/P ratio was high when using all SNPs (0.67) and when only those in the MHC region (0.59), and moderate to low when using all SNPs excluding those in the MHC region (0.39). These results suggest that there is great potential to use antibody response to PRRSV vaccination as an indicator trait to improve reproductive performance in commercial pigs.